Pengaruh Disiplin Kerja Lingkungan Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan Di Kantor Kecamatan Srono Kabupaten Banyuwangi - Pratitha Sungging Parantri; Abdul Kodir Djaelani; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis study aims to determine and analyze the Effect of Work Discipline on Work Environment Work Motivation on the Employee Performance of Srono District Office Banyuwangi partially or simultaneously. The population and sample in this study amounted to 40 people. The data collection technique uses saturated sampling method. Data collection techniques by distributing questionnaires. Analysis of the data used SPSS version 16. The analytical tools used in this study were the Instrument Test, Normality Test, Classical Assumption Test, Multiple Linear Regression Test and Hypothesis Test.Based on the results of this study concluded that the variable Work Discipline affects employee performance, work environment does not affect employee performance and work motivation does not affect employee performance. Simultaneously Variable work discipline work environment and work motivation affect employee performance.Keywords: Work Discipline, Work Environment and Work Motivation